An on-chip nanophotonic reciprocal optical diode for asymmetric transmission of the circularly polarized light. (August 2019) - Fei, Hongming; Wu, Min; Lin, Han; Liu, Xin; Yang, Yibiao; Zhang, Mingda; Cao, Binzhao
Abstract: Here, we theoretically present an on-chip nanophotonic reciprocal optical diode (NROD) for asymmetric transmission of the circularly polarized light, which is a heterostructure comprising two-dimensional (2D) silica and silicon photonic crystals (PhCs). The two 2D PhCs have different effective refractive indices and thus create the asymmetric transmission of the forward and backward incident light. The NROD has a forward transmittance (>0.6) and a high contrast ratio (∼1) in a broad wavelength range (1497 nm～1666 nm). The results deepen the understanding and open up the new possibility in designing novel NRODs for arbitrary polarization states of light. The on-chip NROD will find broad applications in optical communications and quantum computing. Highlights: The designed NROD is able to work with circularly polarization with high performance. The NROD creates the asymmetric transmission of the forward and backward incident light. The performance of the NROD is outstanding due to its high contrast ratio and broad bandwidth. It opens up the new possibilities in designing NRODs for arbitrary polarization states of light.